MANAGING OVERTOURISM THROUGH VIRTUAL TOURISM DURING COVID-19 PANDEMIC - Bafadhal A.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Malang has been officially appointed as the Heritage City, with Heritage Village Kajoetangan as the landmark. The new status adds value to the city yet also brings a risk of overtourism that may disrupt the sustainability of the city. Even though tourist attractions have been reopened in the second quarter of the Covid-19 pandemic, local communities are anxious about tourists visiting their heritage houses. They tend to limit their interactions with visitors, which then decreases their earnings from the tourism sector. This study proposed an alternative solution for this problem by developing a web VR-based virtual tourism. In this Research and Development (R&D), virtual tourism appeared as a strategic visualization suitable to complement the tourism programs in Kajoetangan. Virtual tourism provides a realistic virtual experience that shortens the duration of visits, thereby reducing the visitor flow and controlling overtourism during the Covid-19 pandemic.